“Scanning mutagenesis” of the amino acid sequences flanking phosphorylation site 1 of the mitochondrial pyruvate dehydrogenase complex - Ahsan, Nagib; Swatek, Kirby; Zhang, Jingfen; Miernyk, Ján A.; Xu, Dong; Thelen, Jay (Frontiers in Plant Science, 2012)
The mitochondrial pyruvate dehydrogenase complex is regulated by reversible seryl-phosphorylation of the E1α subunit by a dedicated, intrinsic kinase. The phospho-complex is reactivated when dephosphorylated by an intrinsic PP2C-type protein phosphatase. Both the position of the phosphorylated Ser-residue and the sequences of the flanking amino acids are highly conserved. We have used the synthetic peptide-based kinase client assay plus recombinant pyruvate dehydrogenase E1α and E1α-kinase to perform “scanning mutagenesis” of the residues flanking the site of phosphorylation. Consistent with the results from “phylogenetic analysis” of the flanking sequences, the direct peptide-based kinase assays tolerated very few changes. Even conservative changes such as Leu, Ile, or Val for Met, or Glu for Asp, gave very marked reductions in phosphorylation. Overall the results indicate that regulation of the mitochondrial pyruvate dehydrogenase complex by reversible phosphorylation is an extreme example of multiple, interdependent instances of co-evolution.